2021
DOI: 10.2337/dc21-0131
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Thrombospondin-2 as a Novel Fibrosis Biomarker of Nonalcoholic Fatty Liver Disease in Type 2 Diabetes

Abstract: OBJECTIVE Preclinical studies have suggested that thrombospondin-2 (TSP2) is implicated in liver fibrosis. However, the clinical relevance of TSP2 in nonalcoholic fatty liver disease (NAFLD) remains undefined. Here, we investigated the cross-sectional and longitudinal associations of circulating TSP2 levels with advanced fibrosis (F3 or greater [≥FE] fibrosis) in NAFLD. RESEARCH DESIGN AND METHODS Serum TSP2 levels were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
3
30
1
Order By: Relevance
“…In addition, we found that Th17/Treg was positively correlated with AST, ALT, PCIII, CIV, LN, HA, MDA, and inflammatory factors, and negatively correlated with SOD and GSH-PX by the Pearson correlation coefficient, indicating that elevated Th17/Treg would promote liver injury, hepatic fibrosis, inflammation, and OS. It is well known that hepatic fibrosis appears after almost all chronic liver injuries and is a dynamic process in which various cells such as hepatic parenchymal cells, hepatic stellate cells, hepatic sinusoidal endothelial cells, and a series of cytokine interactions involved jointly mediate the process of hepatic fibrosis, which is a necessary stage of progression to cirrhosis and a common pathological process in many chronic liver diseases [ 23 , 24 ]. Thus, we believe that due to the imbalance of Th17/Treg, hepatocytes can undergo degeneration and necrosis under the long-term inflammatory infiltration and oxidative reaction of lipids, forming a large amount of extracellular matrix (such as noncollagenous glycoproteins and proteoglycans), remaining collagen components, and accumulating in large amounts, which eventually cause fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that Th17/Treg was positively correlated with AST, ALT, PCIII, CIV, LN, HA, MDA, and inflammatory factors, and negatively correlated with SOD and GSH-PX by the Pearson correlation coefficient, indicating that elevated Th17/Treg would promote liver injury, hepatic fibrosis, inflammation, and OS. It is well known that hepatic fibrosis appears after almost all chronic liver injuries and is a dynamic process in which various cells such as hepatic parenchymal cells, hepatic stellate cells, hepatic sinusoidal endothelial cells, and a series of cytokine interactions involved jointly mediate the process of hepatic fibrosis, which is a necessary stage of progression to cirrhosis and a common pathological process in many chronic liver diseases [ 23 , 24 ]. Thus, we believe that due to the imbalance of Th17/Treg, hepatocytes can undergo degeneration and necrosis under the long-term inflammatory infiltration and oxidative reaction of lipids, forming a large amount of extracellular matrix (such as noncollagenous glycoproteins and proteoglycans), remaining collagen components, and accumulating in large amounts, which eventually cause fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our group recently showed that among 682 type 2 diabetes patients from hospital clinics, 8.8% developed AF (defined as LS ≥9.6 kPa) over a median follow‐up period of 1.5 years. Those who were obese, with low platelet count and high hepatic steatosis on VCTE at baseline were at increased risk of incident AF 78 . Therefore, it is recommended that patients with fibrosis at baseline should be monitored at least annually, whereas those without can be monitored every 2–3 years, provided there is no worsening of concomitant metabolic risk factors.…”
Section: Monitoringmentioning
confidence: 98%
“…There have also been suggestions on the direct use of VCTE in fibrosis risk stratification among type 2 diabetes patients 74 . Several recent studies worldwide using VCTE assessments alone have reported a high prevalence of moderate‐to‐advanced liver fibrosis in type 2 diabetes patients, ranging from 15% to 27% 75 , 76 , 77 , 78 . However, VCTE is not widely available in healthcare institutions, and even if it is, given the large volume of type 2 diabetes patients with NAFLD, it is still a challenge to provide timely assessments to all patients with type 2 diabetes in both primary and secondary care sectors.…”
Section: Fibrosis Assessmentsmentioning
confidence: 99%
“…TSP2 was proposed as prognosis marker in liver fibrosis, 47,48 non-alcoholic fatty liver disease, 49 and different cancers. [50][51][52][53] This study demonstrates that TSP2 is an important player in OA pathogenesis, with a positive correlation observed between TSP2 expression and synovial tissue inflammation, suggesting TSP2 could been developed as novel osteoarthritis marker.…”
Section: Discussionmentioning
confidence: 99%